The Impact of Trade Liberalization on Economic Growth in South Africa - Kutu, Augustine Adebayo; Ohonba, Abieyuwa (International Journal of Economics and Financial Issues, 2024)
The failure of the South African economy to achieve the desired economic expansion raised a serious concern to investigate the potency of trade liberalization policy adopted in the country. This is evidence in macroeconomic indices such as high level of unemployment, poverty and most importantly sluggish economic growth. It is against this back drop that this study was spurred to conduct an analysis of the impact of trade liberalization on economic growth in South Africa covering the period of 1986-2022. The mixed order of integration revealed by the unit root test informed the decision to adopt the ARDL method of estimation. The main findings of interest in this study is the existence of a strong positive relationship between trade liberalization and economic growth in South Africa. Thus, the study concludes that economic integration is healthy for the national economy and hence more liberalization policies should be strategically embrace. The study recommends that the African governments especially South Africa should further open it economic border to allow for free trade with other economies of the world.